Nutrition transition, overweight and obesity among rural-to-urban migrant women in Kenya. Issue 17 (4th June 2019) - Peters, Remco; Amugsi, Dickson A; Mberu, Blessing; Ensor, Tim; Hill, Andrew J; Newell, James N; Elsey, Helen
Abstract: Objective: To assess the effect of rural-to-urban migration on nutrition transition and overweight/obesity risk among women in Kenya. Design: Secondary analysis of data from nationally representative cross-sectional samples. Outcome variables were women's BMI and nutrition transition. Nutrition transition was based on fifteen different household food groups and was adjusted for socio-economic and demographic characteristics. Stepwise backward multiple ordinal regression analysis was applied. Setting: Kenya Demographic and Health Survey 2014. Participants: Rural non-migrant, rural-to-urban migrant and urban non-migrant women aged 15–49 years ( n 6171). Results: Crude data analysis showed rural-to-urban migration to be associated with overweight/obesity risk and nutrition transition. After adjustment for household wealth, no significant differences between rural non-migrants and rural-to-urban migrants for overweight/obesity risk and household consumption of several food groups characteristic of nutrition transition (animal-source, fats and sweets) were observed. Regardless of wealth, migrants were less likely to consume main staples and legumes, and more likely to consume fruits and vegetables. Identified predictive factors of overweight/obesity among migrant women were age, duration of residence in urban area, marital status and household wealth. Conclusions: Our analysis showed that nutrition transition and overweight/obesity risk among rural-to-urban migrants is apparent with increasing wealth in urban areas. Several predictive factors were identified characterising migrant women being at risk for overweight/obesity. Future research is needed which investigates in depth the association between rural-to-urban migration and wealth to address inequalities in diet and overweight/obesity in Kenya.